Converter Phenotype: A New Profile That Is Not Exclusive to Taxanes - Jimenez-Rodriguez, Teodorikez Wilfox; Manuel Marco de la Calle, Francisco; Lozano-Cubo, Inmaculada; Montoyo-Anton, Rosa Ana; Soriano-Gomis, Victor; Gonzalez-Delgado, Purificación; Burgos-San José, Amparo; Climent-Ballester, Seira; Martínez-Banaclocha, Natividad; Fernández-Sanchez, Javier (Frontiers in Allergy, 2022)
Introduction: Phenotype I hypersensitivity reactions are the most commonly reported drug reactions; however, precision medicine has made it possible to characterize new phenotypes. A recent communication proposed the existence of a “converter phenotype”, which would affect patients who present non-immediate hypersensitivity reactions and in subsequent exposures develop immediate hypersensitivity reactions. This study aimed to describe the clinical characteristics of converter phenotype reactions and their evolution during desensitization to chemotherapeutic drugs and monoclonal antibodies. Methods: We retrospectively reviewed our database of patients undergoing desensitization to chemotherapy or biological agents and selected those with a converter phenotype. Demographic and clinical characteristics of the patients, the results of skin tests, tryptase and IL-6 levels, and desensitization outcomes were assessed. Results: Of 116 patients evaluated, 12 (10.3%) were identified as having a converter phenotype. The median interval between drug exposure and reaction was 90.6 h (range 8-288 hours). After the conversion, phenotype I was the most frequent (58.3%), followed by cytokine release reactions (33.3%). Fifty-one desensitizations were undertaken and all treatments completed, with 10 (19.6%) breakthrough reactions. No new changes in the phenotype were detected. Conclusions: The symptoms of non-immediate drug hypersensitivity reactions may indicate the need for an early allergological evaluation to assess the risk of future immediate drug reactions. Clinical characteristics, skin test results, and biomarkers can help predict responses to rapid drug desensitization, guiding clinicians on how to optimize therapy delivery while maintaining patient safety.